Trends in streaming video usage at a university during the COVID-19 pandemic. Issue 4 (2nd October 2021) - Foley, Marianne
Abstract: During the coronavirus disease (COVID-19) pandemic colleges and universities in the United States were forced to move to remote delivery of courses and services. Academic library electronic resources naturally adapted to the virtual environment, particularly streaming video. This study considers the trends in academic streaming video usage during the COVID-19 pandemic at a university between March 2020 and May 2021. Challenges for students during the pandemic are also discussed.